Early platelet level reduction as a prognostic factor in intensive care unit patients with severe aspiration pneumonia - Wang, Li-Na; He, Dai-Kun; Shao, Yi-Ru; Lv, Jiang; Wang, Peng-Fei; Ge, Ying; Yan, Wei (Frontiers in Physiology, 2023)
This study investigates risk factors underlying the prognosis of severe aspiration pneumonia (SAP) in intensive care unit (ICU) patients and attempts to provide early prognosis reference for clinical tasks. Patients diagnosed with SAP and admitted to the ICU of Jinshan Hospital, Fudan University, Shanghai, China, between January 2021 and December 2021 were recruited n this retrospective cohort study. Clinical data on a patient’s general condition, underlying diseases, laboratory indicators, and 90-day outcomes (survival or death) were recorded. Multivariate logistic regression analysis showed that a low platelet count is an independent risk factor affecting the prognosis of death (OR=6.68, 95% CI:1.10-40.78, β=1.90, P=0.040). Receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive value of variables; cut-off values were calculated and the area under the curve was 0.7782 [(95% CI:0.686-0.871), P<0.001] for the prediction of death at 90 days in all patients. The Kaplan-Meier curve used for survival analysis showed that, compared with the normal platelet group, the overall survival rate of patients with low platelet levels was significantly lower, and the difference was statistically significant [HR=2.11, 95% CI:1.47-3.03), P=0.0001, z=4.05, X2=14.89]. Cox regression analysis, used to further verify the influence of prognostic risk factors, showed that a concurrent low platelet count was the most important independent risk factor affecting the prognosis of SAP (HR = 2.12 [95% CI:1.12-3.99], X2 = 50.95, P = 0.000). These findings demonstrate an association between SAP mortality and platelet levels on admission. Thus, platelet level at admission may be used as a readily available marker for assessing the prognosis of patients with SAP.